2018
DOI: 10.3390/geosciences8070259
|View full text |Cite
|
Sign up to set email alerts
|

Vegetated Channel Flows: Turbulence Anisotropy at Flow–Rigid Canopy Interface

Abstract: This laboratory study aimed at investigating the mean and turbulent characteristics of a densely vegetated flow by testing four different submergence ratios. The channel bed was covered by a uniform array of aligned metallic cylinders modeling rigid submerged vegetation. Instantaneous velocities, acquired with a three-component acoustic Doppler velocimeter (ADV), were used to analyze the mean and turbulent flow structure. The heterogeneity of the flow field was described by the distributions of mean velocities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
(87 reference statements)
0
17
0
Order By: Relevance
“…The height of the −uw peak for Case II (with vegetation) is higher than the one for Case I (with no vegetation) ( Figure 6a). In Case V, the peak of −uw appears at the canopy level z = h v (Figure 6b) and the free-shear flow happens because of flow discontinuity at the canopy top [10]. within canopy.…”
Section: Shear Stressmentioning
confidence: 97%
See 1 more Smart Citation
“…The height of the −uw peak for Case II (with vegetation) is higher than the one for Case I (with no vegetation) ( Figure 6a). In Case V, the peak of −uw appears at the canopy level z = h v (Figure 6b) and the free-shear flow happens because of flow discontinuity at the canopy top [10]. within canopy.…”
Section: Shear Stressmentioning
confidence: 97%
“…The height of the −uw peak for Case II (with vegetation) is higher than the one for Case I (with no vegetation) (Figure 6a). In Case V, the peak of −uw appears at the canopy level z = hv (Figure 6b) and the free-shear flow happens because of flow discontinuity at the canopy top [10]. The velocity U increases considerably near the channel bed (0 < z < 10 mm) for Cases I & II (Figure 5a & Table 2), which shows the characteristics of the bed-shear flow [8], and dU/dz = 3 s −1 in this region.…”
Section: Shear Stressmentioning
confidence: 99%
“…The upstream cross section of the experimental reclamation channel stretch (indicated as Section 4 in Figure 2) was selected for the flow velocity measurements (mean flow velocity and turbulence fluctuations [16,17]). A 3-component Nortek ® acoustic Doppler velocimeter (ADV) Vectrino II device has been employed, equipped with a 4-beam down-looking probe.…”
Section: Measurements Of the Hydrodynamic Characteristicsmentioning
confidence: 99%
“…The ADV measurement depths from the water surface have been maintained fixed, regardless of the water level registered under each examined flow rates in the vegetated reclamation channel. Many studies dealing with the interaction between water flow and riparian vegetation have been conducted by employing ADV devices, especially in laboratory flumes [17,18], but just in few cases it has been employed in real manmade channels covered by living riparian vegetation [1,5]. An OTT ® C31 propeller-type universal current meter has been located at the downstream cross section of the experimental reclamation channel stretch (indicated as Section 5 in Figure 2) to monitor the water flow velocity aiming at verifying the continuity of the water flow volume in the experimental channel stretch [1].…”
Section: Measurements Of the Hydrodynamic Characteristicsmentioning
confidence: 99%
“…Experimental studies of velocity profiles, like those shown in Figures 3-5, are of much interest; in some cases also the shear stress profiles are studied by means of velocity fluctuant components and Reynolds stress theory [19,[107][108][109][110][111].…”
Section: Methodsmentioning
confidence: 99%